Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences, 2020)
This issue of KIU Journal of Social Sciences focuses on Development Administration, Political Education, Social Psychology, Organizational Management and Educational Technology. The first section of this edition addresses various issues in Development Administration such as rural and community development, International Portfolio Diversification, Remittances, Foreign Aid and Private Consumption, development policies such as Universal Basic Education System, Technical and Vocational Education Programme, Primary Healthcare and Maternal Mortality among others. It is through Development Administration that projects, programs, policies and ideas which are focused at development of a nation, with the point of view of socio-economic and socio-political development of society in general, carried out by talented and skilled bureaucrats. It was revealed in one of the papers in this section that no reasonable rural development can take place without agricultural development and   rural people’s participation in the development efforts meant to develop their communities. The researchers therefore recommended among others that rural development efforts both from the government and Non-governmental organization should give the development of agriculture a priority through agricultural extension. Section two explores Political Education as an instrument of preparing citizens of a country, especially the young, to carry out their civic roles. Political education therefore is the inculcation of the virtues, knowledge, and skills necessary for political participation. Papers, in this second part of the Journal, addresses issues in the concept and perception of citizenship education, role of political parties, peace and security,basic consumers’ rights and utilization among others. Using Edo South Senatorial District in Nigeria as a case study, one of the papers in this section argues that there is no difference between the ways the experienced Social Studies teachers and the less experienced perceived the objectives of Citizenship Education. Based on the result, it is recommended, among others, that there should be full scale implementation of the citizenship education curriculum in schools because of the growing incivility in the country. Section Three focuses attention on Social Psychology. One of the papers in this section establishes that job stress has a significant impact on the integration of one’s family and that families differ in their expectations concerning stress present at work. It therefore suggests that there should be provision for employee training in the area of stress management periodically so that employees can personally be conscious of what they need to do to stay healthy and to stay productive. Papers in the fourth section of this edition center on Organizational Management. Organizational Management helps in Achieving Group Goals. It arranges the factors of production, assembles and organizes the resources, integrates the resources in effective manner to achieve goals. It directs group efforts towards achievement of pre-determined goals. Based on its findings, one of the papers in this section posits that nature of formalization is not significantly correlated with employee performance. And therefore suggests among others that University should encourage hierarchical layer as a means of influencing employees’ performance. Papers in the last section of this edition deal with educational technology. With the help of educational technology, teachers can pay attention to every single student's achievements and they can personalize the educational process. The teacher can also use different methods to capture the students' attention and assess their progress. With that approach, the learning process can be enhanced. That is why one of the papers in this section suggests, as a result of its findings, that the government should provide ICT resources to secondary schools in Nigeria and also educational authorities should lay more emphasis on modern educational resources that promote effectiveness in teaching and learning process. All the articles in this edition of KIU Journal of Social Sciences, in sum, are interesting and well researched. Kudos to the contributors and all members of the editorial board for a job well done.